Ultra-high temperature deformation in a single crystal superalloy: Mesoscale process simulation and micromechanisms. (15th January 2021) - Tang, Yuanbo T.; D'Souza, Neil; Roebuck, Bryan; Karamched, Phani; Panwisawas, Chinnapat; Collins, David M.
Graphical abstract: Abstract: A mesoscale study of a single crystal nickel-base superalloy subjected to an industrially relevant process simulation has revealed the complex interplay between microstructural development and the micromechanical behaviour. As sample gauge volumes were smaller than the length scale of the highly cored structure of the parent material from which they were produced, their subtle composition differences gave rise to differing work hardening rates, influenced by varying secondary dendrite arm spacings, γ ′ phase solvus temperatures and a topologically inverted γ / γ ′ microstructure. The γ ′ precipitates possessed a characteristic butterfly morphology, resulting from the simultaneously active solute transport mechanisms of thermally favoured octodendritic growth and N-type rafting, indicating creep-type mechanisms were prevalent. High resolution-electron backscatter diffraction (HR-EBSD) characterisation reveals deformation patterning that follows the γ / γ ′ microstructure, with high geometrically necessary dislocation density fields localised to the γ / γ ′ interfaces; Orowan looping is evidently the mechanism that mediated plasticity. Examination of the residual elastic stresses indicated the butterfly γ ′ precipitate morphology had significantly enhanced the deformation heterogeneity, resulting in stress states within the γ channels that favour slip, and that encourage further growth of γ ′ precipitate protrusions. The combination of such localised plasticity and residual stresses are considered to be critical in the formation of the recrystallisation defect in subsequent post-casting homogenisation heat treatments.